Adams and Eves: The Gender Gap in Economics Majors - Graziella Bertocchi; Luca Bonacini; Marina Murat (Institute of Labor Economics (IZA), 2021)
We investigate the gender gap in Economics among bachelor's and master's graduates in Italy between 2010 and 2019. First we establish that being female exerts a negative impact on the choice to major in Economics: at the bachelor level, only 73 women graduate in Economics for every 100 men, with the mathematical content of high school curricula as the key driver of the effect and a persistence of the gap at the master level. Second, within a full menu of major choices, Economics displays the largest gap, followed by STEM and then Business Economics. Third, decomposition analyses expose a unique role for the math background in driving the Economics gender gap relative to other fields. Fourth, a triple difference analysis of a high school reform shows that an increase in the math content of traditionally low math curricula caused an increase in the Economics gender gap among treated students.
Keywords: A22; I23; J16; 330; education gender gap; economics; higher education; business economics; major choice; major switching; mathematics; stereotypes